2020
DOI: 10.5194/amt-13-6427-2020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of optical particulate matter sensors under realistic conditions of strong and mild urban pollution

Abstract: Abstract. In this paper we evaluate characteristics of three optical particulate matter sensors/sizers (OPS): high-end spectrometer 11-D (Grimm, Germany), low-cost sensor OPC-N2 (Alphasense, United Kingdom) and in-house developed MAQS (Mobile Air Quality System), which is based on another low-cost sensor – PMS5003 (Plantower, China), under realistic conditions of strong and mild urban pollution. Results were compared against a reference gravimetric system, based on a Gemini (Dadolab, Italy), 2.3 m3 h−1 air sam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 47 publications
1
26
0
1
Order By: Relevance
“…The BAM PM analyzers employ the absorption of beta radiation by solid particles extracted from air flow [3]. These analyzers have gone through strict field evaluations and demonstrated that they could provide concentration measures equivalent to the filter-based GMM, with the advantage of being usable for continuous PM monitoring (generally with a temporal resolution of 1 h) [5]. Finally, the optical sensors measure particles' size by light scattering, so the concentration of PM can be detected according to the signal [3,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The BAM PM analyzers employ the absorption of beta radiation by solid particles extracted from air flow [3]. These analyzers have gone through strict field evaluations and demonstrated that they could provide concentration measures equivalent to the filter-based GMM, with the advantage of being usable for continuous PM monitoring (generally with a temporal resolution of 1 h) [5]. Finally, the optical sensors measure particles' size by light scattering, so the concentration of PM can be detected according to the signal [3,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The event of mineral dust incursion from Central Asia herein described occurred at the end of March 2020 and, to the best of our knowledge, has not been so far the object of an in-depth analysis though it was mentioned in a few papers devoted to other topics (Masic et al, 2020;Šikoparija, 2020) or described qualitatively in remote sensing or meteorological web pages (Mahovic et al, 2020;SNPA, 2020).…”
mentioning
confidence: 97%
“…Several studies examining the performance of the Grimm 11-D unit under diverse atmospheric and laboratory conditions have found it to be comparable to various reference units (Masic et al, 2020;Vasilatou et al, 2021). For example, Masic et al (2020) found that it performed well under diverse atmospheric and pollution conditions; when equipped with a dryer, it performed at a level comparable to that of a reference unit (a beta attenuation monitor).…”
Section: Instruments Used In the Aerosol Measurements Unitmentioning
confidence: 87%
“…These are made available through a Grimm proprietary algorithm, but the manufacturer does not share information about it, or the refractive index, density, and weighting factors used for the calculations. The Grimm 11-D and previous versions have been used in various indoor (Mølgaard et al, 2015) and atmospheric studies (Mukherjee et al, 2017;Stavroulas et al, 2020;Masic et al, 2020), including under dusty conditions (Jaafari et al, 2018). Several studies examining the performance of the Grimm 11-D unit under diverse atmospheric and laboratory conditions have found it to be comparable to various reference units (Masic et al, 2020;Vasilatou et al, 2021).…”
Section: Instruments Used In the Aerosol Measurements Unitmentioning
confidence: 99%
See 1 more Smart Citation